Analysis of on-time delivery performance from inbound logistics, operations, and outbound logistics - Chuasuksanthong, Veerawithe; Duantrakoonsil, Wanwisa; Janyapoon, Suwat (Edelweiss Applied Science and Technology, 2025)
This research aims to study the logistics and transportation management of Sattel (Thailand) Co., Ltd., a company engaged in domestic freight transport. A mixed methods research approach was employed, combining both qualitative and quantitative analyses. The qualitative research involved in-depth interviews and field observations, while the quantitative component utilized data from ERP and distribution requirements planning (DRP) systems, as well as vehicle routing problem (VRP) techniques for route optimization. The findings indicate that key factors influencing transportation performance include route planning, vehicle resource management, real-time shipment tracking, and communication among relevant departments. The main challenges identified were suboptimal route planning, leading to delivery delays, workforce shortages during peak periods, and ineffective coordination across inbound logistics, operations, and outbound logistics. To enhance transportation efficiency, the study proposes several strategies: implementing systematic transport route planning using appropriate route optimization technologies; improving the flexibility of vehicle resource allocation; adopting comprehensive real-time shipment tracking systems; and strengthening coordination processes among all involved parties. These improvements are expected to increase delivery punctuality, reduce delays, and elevate the overall performance of the logistics system.